Characterizing Heterogeneous Processes of Water Flow and Solute Transport in Soils Using Multiple Tracer Experiments. Issue 3 (1st July 2013) - Wang, Kang; Zhang, Renduo; Sheng, Feng
Abstract : It is important yet challenging to adequately describe heterogeneous flow processes in soils. The objectives of this study were to "visualize" heterogeneous processes of water flow and solute transport in soils by using multiple tracers and to quantify heterogeneities of soil water flow and solute transport by using a discrete random cascade model. Field tracer experiments on two soils were conducted with sequences of iodine–nitrate and iodine–bromide mixtures. On the basis of the experimental data, a random cascade model, an annular histogram, and a similarity index were applied to characterize the heterogeneous flow and transport processes in the soils. Results showed that water and solute penetrated into deep soil preferentially mainly because of the macropore flow. At the beginning of infiltration, the solute transport heterogeneity was mainly related to the saturation process of soil macropores. As more water infiltrated into the soil, the solute transport heterogeneity was mainly attributable to the change of flow paths. After the macropores were saturated, unstable infiltration fronts resulted in the transport heterogeneity. The experimental data and analyses of the random cascade model demonstrated that the solute transport process included more heterogeneous information than the heterogeneous water flow, which was related to the soil heterogeneity, water flow heterogeneity, and the heterogeneity of the solute transport itself.